2016
DOI: 10.1177/0025817216669092
|View full text |Cite
|
Sign up to set email alerts
|

Financial and legal decision-making capacity in the aphasic population – a narrative review

Abstract: Whilst a significant amount of research has been done on decision-making capacity, it is mostly focused on healthcare; in particular, on patient consent for treatment for the non-aphasic population. Although a communication aid exists to aid assessment of decision-making capacity for healthcare for aphasic individuals, no similar tools exist to aid financial and legal decision-making capacity assessments. This paper highlights an important problem encountered during clinical practice which requires further res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…No communication aid currently exists to support financial decision-making capacity (DMC) assessments for persons with aphasia (PWA). (1) We sought to establish the validity, reliability, and feasibility of a newly constructed communication aid desigqned for this purpose.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No communication aid currently exists to support financial decision-making capacity (DMC) assessments for persons with aphasia (PWA). (1) We sought to establish the validity, reliability, and feasibility of a newly constructed communication aid desigqned for this purpose.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of communication disorders, like aphasia, such assessments become challenging and require the use of a dedicated communication aid.No communication aid currently exists to support financial decision-making capacity (DMC) assessments for persons with aphasia (PWA). (1) We sought to establish the validity, reliability, and feasibility of a newly constructed communication aid desigqned for this purpose.…”
mentioning
confidence: 99%
“…7 No similar communication aids are available for other types of decision making. 8 The majority of research in DMC has been focused on patient consent within healthcare, with considerably less focused on financial DMC, almost all of which is related to understanding the financial decision-making process and how this becomes impaired in the context of certain neurodegenerative and psychiatric conditions. There is currently no research around financial DMC and aphasia, leaving a significant knowledge gap.…”
mentioning
confidence: 99%
“…There is currently no research around financial DMC and aphasia, leaving a significant knowledge gap. 8 Interestingly, despite the significant negative consequences that can arise following the assessment of financial DMC for aphasic individuals, no formal legislation exists dictating the role of communication supports within the DMC assessment process. 9 This has resulted in an absence of communication aids to support such assessments and a worrying knowledge-practice gap that is concerning for both medical and legal professions.…”
mentioning
confidence: 99%
“…There is a substantial literature addressing competency, decision-making capacity, and selfdetermination focusing on individuals with dementia, intellectual and developmental disabilities, psychiatric disturbances, and aphasia. [23][24][25][26][27] In comparison, relatively less attention has been directed to self-determination in PPA. Le Rhun and colleagues 28 reported that individuals with PPA who had high Mini-Mental State Examination scores, moderate aphasia, and fluent language on baseline clinical assessment subsequently retained greater autonomy in daily life.…”
mentioning
confidence: 99%